Escala de ambiguidade - Alves, Tania Maria Oliveira (1985)
The purpose of this work was to create an instrument to measure the ambiguity level as showed by individuals on common day by day situations. Ambigui ty level is expressed as the person capacity to create ambiguity when facing determined social situations. This work has arisen as a consequence of the doctorate thesis 'Anomia e Desorganização: estudo psicológico em contexto brasileiro', presented in 1981 and whose results, faced with the daily reality, pointed out the ambiguous model caracteristical of our society, showed up in the form of several contradictions in people attitudes. Ambiguity seems to be found in the system as the result of the interpretation one gives to ambiguous patterns, laws, rules and values or yet as consequence of the violation itself or lack of information of the ru1es, the constant reformulations, the lack of trust and of the social adaptation in a general way. The theoretical approach was based mainly on social and anthropologic theories which propose the reality as something built by the person being the ambiguous behavior the resultant of the interrelation between the person and the social environment in which he lives. In order to back-up the scale, two factors have been isolated: (1) the ambiguity as a social factor and (2) the ambiguity as a psychological factor.